A Review of the Impact of Artificial Intelligence on Traditional Accounting Practices and Financial Reporting - Abdullahi Ya'u Usman; Sulaiman Taiwo Hassan; Abalaka James Nda; Yusuf Adeyanju Yisau (International Journal of Science and Society (IJSS), 2025)
This study investigates the transformative effects of Artificial Intelligence (AI) on conventional accounting practices, focusing on its influence in reshaping financial reporting, auditing, and decision-making frameworks. Positioned within the context of rapid technological progression, the research traces the shift from traditional, manual accounting processes to advanced AI-enabled systems. The objective is to critically evaluate how AI adoption is redefining the accounting profession, identifying both the opportunities it offers and the challenges it poses. A systematic literature review and bibliometric analysis were conducted, drawing from peer-reviewed journals, case studies, and industry publications from the past ten years. This comprehensive methodology facilitates a deep understanding of AI’s role in accounting, particularly in enhancing accuracy, efficiency, and strategic capabilities within the field. Results indicate that AI significantly boosts the precision and speed of financial operations by automating repetitive tasks and providing predictive insights for more informed decision-making. Nonetheless, the implementation of AI faces several obstacles, including the demand for technically skilled professionals, concerns surrounding data security, high implementation costs, and organizational resistance to change. The study concludes by advocating for a measured and strategic approach to AI integration. Emphasis is placed on continuous professional development, ethical considerations, and adherence to regulatory standards. While the transition presents challenges, the potential of AI to transform accounting practices and drive innovation in the digital age is substantial.